Evaluation of the Effect of Blades Number on the Performance of Pico Wind Turbines - Yasir Abood; Tariq A. Ismail; Omar A. Abdulrazzaq; Haider S. Hussein (Iraqi Journal of Industrial Research)
In this paper, the influence of blades number on the performance of pico wind turbine was investigated by using a small-motorized axial DC fan with a rated power of 4W. Fixed streaming air blower was used as a source of wind. Varying in wind speed was accomplished by changing the distance from the blower. A resistor equals to the turbine internal resistance was utilized as a load to collect the electrical power across the load at various wind speeds and for fans of different blades (1, 2, and 5). Values of the cut-in and cut-out speeds were extracted from the power plot. Rated power was recorded, as well. The results have shown that the rated power generated by turbine has decreased due to the reduction of blades number (i.e., reduction in solidity) from 2.6W for a 5-bladed turbine to 0.665W for a 2-bladed turbine and to 0.13W for a 1-bladed turbine. Moreover, the cut-in speed (initial electrical generating speed) has increased from 4.9m/s for 5-bladed to 8m/s for 2-bladed, then to 19.15m/s for 1-bladed. These results are explained by the balancing problems during rotation (polar asymmetrical rotor), and it is seen that the reduction of blades has made a sharp reduction in power coefficient.